Extracellular complex of beta‐amyloid with glyceraldehyde‐3‐phosphate dehydrogenase contributes to neurodegeneration in Alzheimer's disease: Molecular and cell biology/APP/Abeta/amyloid. (7th December 2020) - Kozin, Sergey A.; Lazarev, Vladimir; Tsolaki, Magda; Mikhailova, Elena; Benken, Konstantin; Shevtsov, Maxim; Nikotina, Alina; Mitkevich, Vladimir; Makarov, Alexander; Margulis, Boris; Guzhova, Irina
Abstract: Background: The discovery of migrating protein complexes armed with β‐amyloid (Aβ) and acting as the driving force of Alzheimer's disease (AD) mechanism led us to suggest that besides the pathogenic peptide some other proteins may cooperate with the latter and enhance its cytotoxicity and intercellular propagation. One of such proteins was suggested to be glyceraldehyde‐3‐phosphatedehydrogenase (GAPDH), enzyme that in normal conditions maintains cellular glycolysis and under action of oxidative stress is converted to monomers and dimers and forms tight, insoluble complexes with aggregation‐prone polypeptides. Method: CSF samples were collected from patients of both genders. The cohort comprised four patient groups: (1) mild cognitive impairment (MCI) n = 21; (2) mild AD‐type dementia ('Mild'), n = 58; (3) moderate AD‐type dementia ('Moderate') n = 57; and (4) severe AD‐type dementia ('Severe'), n = 56. The diagnosis was established according to the NINCDS‐ARDRA criteria for AD and the Petersen criteria for MCI. Patients were assigned to severity subgroups based on their scores on the Mini‐Mental State Examination (MMSE). Two animal models of AD were used in this study: (1) "chemical" model in rats and (2) transgenic 5XFAD mice. Result: GAPDH is present in cerebrospinal fluid samples of AD patients as covalent complex with Aβ, and the heavier the stage of the disease, the higher is the level of such complexes. The increase of constitutional GAPDH level in AD animal models results in aggravation of cognitive and brain deficits linked to AD progression. Conclusion: The findings imply a potential role of GAPDH as biomarker and prerequisite of massive neuronal death on the late stages of Alzheimer's disease Supported by RSF grant #19‐74‐30007.